The Victimization of the Ahmadiyya Minority Group in Indonesia: Explaining the Justifications and Involved Actors - Max Regus (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2020)
This article discusses the victimization of the Ahmadiyya minority community in Indonesia. This article can be considered as one of the crucial studies that analyze the problems faced by the Ahmadiyah minority group in Indonesia due to violence. This study's importance relates to academic efforts in understanding the complexities of the Ahmadiyya community's victimization in Indonesia. This study is also essential in providing input or recommendations for the state, social elements (NGOs), and the Ahmadiyah group. This article proposes the theory of violence as an analytical framework for understanding violence against the Ahmadiyah group. This article provides vital objectives in understanding two aspects of the victimization process of the Ahmadiyya group. First, justifications for the victimization is based on state and religious decrees. Second, the victimization process involves actors and institutions. Besides, this study was conducted using a systematic qualitative review as a method. The data has been collected through extensive reviews on previous studies, ethnographic reports, institutional reports, NGO reports, government, and media.